Changes on the Climatic Edge: Adaptation of and Challenges to Pastoralism in Montesinho (Northern Portugal) - José Castro (International Mountain Society, 2021)
Mountain areas are sensitive to changes in precipitation and temperature, which significantly impact traditional pastoralist communities, their economy, and their lifestyle. Alarming climate change scenarios justify the investigation of the ecological and socioeconomic vulnerabilities that characterize Portugal's mountain regions. This work explores how the traditional production systems of small ruminants—sheep and goats—could adapt in the Montesinho mountain range as it changes over the next 2 decades. Land use–land cover maps from 1995 and 2018 show how the pastoral landscape has changed and indicate trends for a future scenario. Documented landscape grazing patterns are used to determine sheep and goat landscape preferences under different climatic conditions. Finally, we identify the near-future constraints on traditional sheep and goat systems, contrasting landscape changes with sheep and goat preferences. Over coming decades, the balance between rangelands and cultivated lands will persist in the Montesinho mountain landscape, despite some trade-offs between both. Woodlands could emerge from scrublands colonizing rangelands, and permanent crops could significantly replace arable lands in agricultural areas. Therefore, it is likely that the agricultural areas preferred for sheep, and rangelands preferred for goats, may not be affected by the forecast landscape changes, but rather be favored by the expansion of permanent crops. However, pasture areas must expand, as they are key to pastoral landscape function in a warming climate scenario. Landscape decision makers and managers should implement a landscape-monitoring system to inform policies and strategies aimed at protecting and safeguarding mountain pastoralism and its vital ecosystem services.